Assessing dysplasia/cancer in large non-granular and homogenous granular laterally spreading tumors: Optical evaluation versus forceps biopsy - Tkachov, V. S.; Kiosov, O. M.; Klymenko, A. V.; Ткачов, Владислав Сергійович; Кіосов, Олександр Михайлович; Клименко, Андрій Володимирович (My University, 2024)
Aims Evaluate the precision of dysplasia/cancer detection using forceps biopsy( FB) compared to optical evaluation methods for homogenous granular and non-granular subtypes of large laterally spreading tumors (LSTs), aligning their outcomes with histopathological findings.
Keywords: тези доповідей